Syringoma: A rare presentation at an unusual site - Anitha Bhakthavatsalam; Ragunatha Shivanna (Wolters Kluwer Medknow Publications, 2021)
Syringomas are benign adnexal tumors arising from the lower intraepidermal and upper dermal eccrine sweat ducts, manifesting as asymptomatic, multiple tiny firm skin-colored papules, commonly over the lower eyelid and malar area of the face. A case of syringoma in an adult female patient presenting with asymptomatic lesions occurring exclusively on the vulva with an unusual presentation as a polypoidal growth is reported. Vulvar syringomas may not be recognized if they are asymptomatic or they may be misdiagnosed. Examination of the vulvar region should not be missed when syringoma is found outside the genital area. Syringomas should be considered in the differential diagnosis of vulvar pruritus, vulvar pain syndrome, and papulonodular lesions or polypoidal mass over the vulva.